A Means of First Resort: Explaining "Hot Pursuit" in International Relations. (3rd July 2018) - Beehner, Lionel M.
ABSTRACT: This article provides a new theory of hot pursuit—the use of military force by a state against a nonstate actor across borders—in international relations. Drawing from the literature on civil-military relations, I argue that attitudes on limited use of force in peripheral areas will vary between civilian and military, with the latter preferring to treat hot pursuit as a policing operation, whereas the former will treat it as a military one. The logic of my argument is that militaries are oriented structurally and culturally to fight conventionally and against state near-peer adversaries. Threats emanating from nonstate actors, while at times perceived to be existential, require "pin-prick"-style targeted airstrikes, raids by commando forces, or policing operations along a state's periphery. I draw on an original dataset of "hot pursuit" (1975–2009) I collected and examine two recent case studies: India's hot pursuit of ethnic militants into Myanmar and Turkey's pursuit of Kurdish militants into Iraq and Syria.